CAR 2025 Reviewer Recognition / Reconnaissance des réviseurs 2025 de RCC (Contemporary Accounting Research, 2025)
Beginning May 1, 2020, with the strong support of our team of Editors, CAR implemented a reviewer recognition program.The purpose of the program is to annually recognize reviewers, nominated by the Editors, who regularly perform exceptionally high-quality and timely reviews.CAR has a long-standing tradition of providing thoughtful and constructive reviews